Low-power-consumption optical interconnect on silicon by transfer-printing for used in opto-isolators. (30th November 2018) - Liu, Lei; Loi, Ruggero; Roycroft, Brendan; O'Callaghan, James; Trindade, Antonio Jose; Kelleher, Steven; Gocalinska, Agnieszka; Thomas, Kevin; Pelucchi, Emanuele; Bower, Christopher A; Corbett, Brian
Abstract: On-chip optical interconnects heterogeneously integrated on silicon wafers by transfer-print technology are presented for the first time. Thin (<5 µ m), micron sized light-emitting diodes (LEDs) and photo diodes (PDs) are prefabricated and transfer-printed to silicon wafer with polymer waveguides built between them. Data transmission with total power consumption as low as 1 mW, signal to noise ratio of >250 and current transfer ratio of 0.1% in a compact volume of <0.0004 mm 3 are demonstrated. Experiment shows that the polymer waveguide between the LED and PD plays a key role in enhancing the data transmission efficiency. Reciprocal performance for bidirectional transmission is also achieved. The results show the potential for cost-effective and low profile form-factor on-chip opto-isolators.